Experiences of Volunteers in Refugee Resettlement - Rita B. Thomson (Journal of Public and Professional Sociology, 2014)
This paper examines the experiences of volunteers mentoring refugees resettled in the Atlanta area. Every year since 1980, the United States has resettled people who have been defined as refugees by the United Nations. Refugees come with few material resources and bring even greater ethnic variation into the country than other immigrants do. The federal government contracts with voluntary, non-governmental agencies to do the resettlement. Because of limited staff and funding, these agencies rely on volunteers to help in the resettlement process. This study describes the experiences of ten volunteers of varied age, race, and religion who have mentored refugee families. Most volunteers were first introduced to refugees either by a friend or by a church activity. They chose to mentor because of the teachings of their faith, a desire to impact the community, and empathy for the refugees. Volunteers developed friendships with the refugees while explaining American culture, guiding them to local facilities, and enjoying recreational activities. In spite of some difficulties, all the volunteers felt rewarded by love and friendship. All volunteers desired to repeat the mentoring experience and several sought even greater involvement in assisting refugees. In general the volunteers feel that refugees will successfully become Americans.